Phase analysis of biphoton joint spectra by interference between different SPDC sources - Hurvitz, Inbar; Shukhin, Anatoly; Vidro, Leonid; Eisenberg, Hagai; Arie, Ady (Optica Quantum, OPTICAQ, 2024)
In spontaneous parametric down-conversion, the spectral correlations between the signal and the idler are expressed by the joint spectral amplitude (JSA) function. However, in the standard coincidence measurements, the phase information of the JSA is lost, and only the square of the absolute value of the JSA is recorded, thus preventing full characterization of the biphoton state. Here, we present an experimental technique to investigate the interference of biphoton joint spectral amplitudes, unlocking new avenues in quantum photonics research. Our method explores phase-dependent phenomena within entangled biphoton spectra. This is achieved by simultaneously pumping two structured nonlinear photonic crystals and observing their interference, which reveals previously inaccessible effects with direct intensity measurements. We demonstrate the versatility of our technique by analyzing two types of joint spectra: one exhibiting a two-lobe shape and the other a three-lobe shape. Additionally, we reconstruct the joint spectral amplitudes for both scenarios and observe good agreement with theoretical predictions. These results pave the way for developing advanced quantum communication and information processing technologies using biphoton spectra.
Publisher: Optica Publishing Group
Keywords: Nonlinear effects; Nonlinear photonic crystals; Quantum communications; Quantum key distribution; Spectral properties; Superconducting nanowire single photon detectors